Quest of participatory forestry in Terai (Morang experiences) - Baral, Jagadish C; Shrestha, Madan Kumar; Sharma, Khil Prasad (Banko Janakari, 2008)
Terai witnesses a deadlock syndrome as far as the region’s forest resource governance is concerned. While the government advocates for what has been termed ‘collaborative forest management’ modality for the Terai, Federation of Community forest User Group (FECOFUN), the umbrella institution of over 14,000 hitherto existing community forestry groups vehemently opposes the move. It assumes that community forestry modality has stood the test of the time and that it is not worthwhile to even consider any alternative resource governance modality, be it in the hills or the Terai. The tension is on the rise and that the deadlock situat6ion persists. This has increasingly pushed the resource there into accelerated state of degradation as a viable local institution that takes care of it is not in place.For the past two years, we in Morang district are trying to figure out whether this deadlock scenario can be broken by way of innovating a consensus based modality that could satisfy all concerned parties. Forum for Forestry Stakeholders (FFS), a multistakeholder platform, forms the focal point of the overall endeavour. The paper starts off by presenting a background on the current state of deadlock situation followed by introduction of forest and forestry practices in Morang. It will then move on to the processes through which the multistakeholder forum was formed that will be followed by key features on the forum and its major undertakings so far. Key findings to date and the vision for the future are presented which forms an important segment of the paper.Key words: Forest Resources; Participatory forestry; Terai; NepalBanko Janakari Vol.16(2) 2006 pp.50-57